RITUXIMAB AMELIORATES SKIN FIBROSIS THROUGH REGULATING MYOFIBROBLASTIC ACTIVITY AND TGF-?1 DIFFERENTIATION IN BLEOMYCIN-INDUCED EXPERIMENTAL SCLERODERMA MODEL - Karatas, Ahmet; Dik, Yavuz; Ozgen, Metin; Oz, Burak; Onalan, Erhan; Gozel, Nevzat; Koca, Suleyman S. (Parlar Scientific Publications (P S P), 2021)
Scleroderma (systemic sclerosis) is a chronic inflammatory disease that progresses with vascular damage. immunological abnormalities, and extensive fibrosis. Rituximab, an antibody against the B-lymphocyte-specific CD20 surface marker leads to depletion of B cell counts and functions. This study aims to investigate the protective efficacy of rituximab on skin fibrosis in bleomycin (BLM)-induced experimental scleroderma model,This study included 4 groups of (n=7 for each group)Balb/c mice. Group I mice were treated with subcutaneous 100 mu l/day phosphate-buffered saline (PBS); while mice in Groups II, III, and IV were treated with subcutaneous 100 mu l/day BLM. Mice in Group III and Group IV were treated, intraperitoneally, with 50 mu g and 250 mu g rituximab, respectively; on the 1st and 14th days of the experiment, Mice in all groups were sacrificed at the end of the 4-week experimental period and tissue specimens were obtained. Serum levels of transforming growth factor (TGF)-beta 1, dermal thickness, the number of dermal inflammatory cells, and the number of alpha smooth muscle actin positive cells (alpha-SMA+) were determined,The administration of BLM increased the inflammatory cell infiltration of the dermis, alpha-SMA+ cell counts in the dermis, and dermal thickness. However, rituximab treatments decreased inflammatory cell infiltrations, alpha-SMA+ cell counts and dermal thickness, in the BLM injected mice. Both rituximab doses had similar anti fibrotic efficacy. Rituximab prevents the development of fibrosis in a BLM-induced experimental scleroderma model. This result suggests that rituximab may be a effective therapeutic agent in patients with early-stage scleroderma.
Keywords: Scleroderma; bleomycin; rituximab